Amaranth as a Dual-Use Crop for Leafy Greens and Seeds: Stable Responses to Leaf Harvest Across Genotypes and Environments - Hoidal, Natalie; Díaz Gallardo, Maria; Jacobsen, Sven-Erik; Alandia, Gabriela (Frontiers in Plant Science, 2019)
Dual-use production systems that utilize the green leaves as well as seeds from amaranth are highly promising for small-scale farmers around the world. The leaves are an important source of nutrients for farming families, while seeds can provide income. Farmers who use amaranth as a dual-use crop are concerned about the impacts of defoliation on seed yield. This experiment tested defoliation at various intensities and frequencies (0, 25, 50, 75, and 100% defoliation, 1, 2, and 3 times) under controlled conditions as well as under Danish and Mexican field conditions. Defoliation tolerance was tested in a total of seven varieties, spanning the three primary grain amaranth species: A. cruentus, A. hypocondriacus, and A. caudatus. In all of the varieties and environments tested, we found that neither seed yield nor quality was impacted by a single defoliation event at intensities up to 50% leaf removal. We observed similar responses with two and three consecutive defoliations in which we removed 25% of all leaves. Greater frequency and intensity of defoliation resulted in reduced seed yield in some environments, while seed quality (protein content and 1000 KW) did not appear to be affected. Dual-use production systems should be promoted with small-scale farmers around the world as promising systems for improving local nutrition while maintaining profits from seed production. This paper provides baseline guidelines for farmers regarding optimal defoliation intensities and frequencies.